Over-expression, purification and biochemical characterisation of trypanosomal heat shock protein - Edkins, Adrienne Lesley (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2003)
The molecular chaperone process of assisted protein folding, characteristic of members of the Heat Shock Protein 70 kDa (Hsp70) and Heat Shock Protein 40kDa (Hsp40) families, is essential for cytoprotection in stressful cellular conditions. Examples of such conditions are heat shock or invasion by pathogens. The Hsp70/Hsp40 process of assisted protein folding is dependent on ATP (governed by the intrinsic ATPase activity of Hsp70) and the ability of molecular chaperones to recognise and bind non-native protein conformations. Here, we analyse and attempt to characterise the molecular chaperone activity of an inducible, cytoplasmic Hsp70 (TcHsp70) from Trypanosoma cruzi and its interactions with its potential partner Hsp40s, Tcj 1, Tcj2, Tcj3 and Tcj4. A bioinformatic analyses of the primary sequences of the trypanosomal proteins revealed that they all contained the canonical domains that define other members of the Hsp70 and Hsp40 family. Tcj2 and Tcj4 showed deviations from the consensus sequence in their substrate binding regions, which may have implications for their substrate binding specificities. TcHsp70, Tcj 1, Tcj2, Tcj3 and Tcj4 were over-expressed recombinantly as 6xHis-tag fusion proteins in Escherichia coli. His-TcHsp70, Tcjl-His and His-Tcj2 were successfully purified by Nickel-affinity chromatography for functional analyses to assess the molecular chaperone activity of His-TcHsp70 in terms of its ATPase activity and substrate binding ability. The basal ATPase activity of His-TcHsp70 was determined as 40 nmol Pi/min/mg, significantly higher than that reported for other Hsp70s. This basal ATPase activity was stimulated to a maximal level of 60 nmol Pi/min/mg in the presence of His-Tcj2 and a model non-native substrate, reduced carboxymethylated Î±x-lactalbumin (RCMLA). Using native polyacrylamide gel electrophoresis and Western analysis, His-TcHsp70 was shown to form discrete complexes when in the presence of Tcj 1- His, His-Tcj2 and/or RCMLA. These complexes potentially represent His-TcHsp70 - RCMLA or His-TcHsp70 - Tcj interactions, that may be indicative of chaperone activity. In vivo complementation assays showed that Tcj2, but not Tcj3, was able to overcome the temperature sensitivity of the ydjJ mutant Saccharomyces cerevisiae strain JJ160, suggesting that Tcj2 may be functionally equivalent to the yeast Hsp40 Ydj1.
Keywords: Heat shock proteins; Heat shock proteins -- Structure activity relationships